(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
Noble dental alloys are often reused in dental practice by recasting. The aim of this study was to determine if repeated casting of high gold dental alloys has a detrimental effect on alloy microstructure, type of porosity, structure and microhardness. Results, obtained during the presented investigations, showed that recasting procedure had a strong effect on the change of alloy porosity type. Also, results showed that alloy microhardness increased with the increase of the number of recasting cycles. At the same time the grain growth and changes of the solid solution type in the alloy microstructure were observed.